Biocontrol of Sclerotinia sclerotiorum (Lib.) de Bary on common bean by native lipopeptide-producer Bacillus strains - Sabate, Daniela Constanza (2018)
Bacillus sp. B19, Bacillus sp. P12 and B. amyloliquefaciens B14 were isolated from soils of Salta province, and PGPR properties on the common bean (Phaseolus vulgaris L.) cv. Alubia and antagonistic activity against Sclerotinia sclerotiorum were studied. It was determined that B19 and P12 increased crop germination potential (GP) from the common bean by 14.5% compared to control seeds; these strains also increased root length (10.4 and 15%, respectively) and stem length (20.2 and 30%, respectively) compared to the control; however, as for the B14 strain, no increases in growth parameters were detected. In addition, all the treatments that combined two bacilli: B14 + B19, B14 + P12 and B19 + P12, generated beneficial effects on GP and seedling growth compared to control seeds, but not compared to a single inoculant. B19 and P12 strains synthesized auxins at concentrations of 5.71 and 4.90 mg/mL, respectively, and it was qualitatively determined that they synthesize siderophores. In addition, previous studies have determined that B14 produces auxins in a concentration of 10.10 mg/mL, and qualitatively synthesizes siderophores. The phytosanitary state of the white bean cv. Alubia control seeds revealed bacterial contamination in 87% of all the evaluated seeds and different fungi such as Cladosporium sp., Fusarium sp., and Rhizopus sp. Bean seeds treated with B14, B19 or P12 showed no growth of contaminating bacteria or of pathogenic fungi; in fact, bacilli inoculum development was observed in all seeds. Additionally, B19, P12 and B14 strains inhibited in vitro the development of 9 native S. sclerotiorum strains isolated from the Salta region, with FI ranging between 60 and 100%. The three Bacillus strains synthesized different isoforms of the lipopeptides: surfactin, iturin, and fengycin in the presence of S. sclerotiorum, as determined by MALDI-TOF. In the in vivo trials, when common bean seeds were grown in soils contaminated with S. sclerotiorum, an incidence of 100% was determined when the seeds were not treated with any Bacillus. Seeds treated with the chemical fungicide and sown in S. sclerotiorum-infested soil did not produce seed emergence, while the inoculation of the seeds with B14 + P12, B14 + B19 or B19 + P12 reduced the effect of the pathogen by 46, 43 and 25%, respectively. Disease progression in B14 + P12 and B14 + B19 treatments was significantly lower than in the remaining treatments, with an AUDPC of 873.75 and 1071, respectively.